Adenocarcinoma classification: patterns and prognosis - KUHN, E.; MORBINI, P.; CANCELLIERI, A.; DAMIANI, S.; CAVAZZA, A.; COMIN, C.E. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Lung cancer is the most frequent human malignancy and the principal cause of cancer-related death worldwide. Adenocarcinoma is now the main histologic type, accounting for almost half of all the cases. The 2015 World Health Organization has adopted the classification recently developed by the International Association for the Study of Lung Cancer, American Thoracic Society, and European Respiratory Society. This new adenocarcinoma classification has incorporated up-to-date advances in radiological, molecular and oncological knowledge, providing univocal diagnostic criteria and terminology. For resection specimens, new entities have been defined such as adenocarcinoma in situ and minimally invasive adenocarcinoma to designate adenocarcinomas, mostly nonmucinous and ≤ 3 cm in size, with either pure lepidic growth or predominant lepidic growth with ≤ 5 mm invasion, respectively. For invasive adenocarcinoma, the new classification has introduced histological subtyping according to the predominant pattern of growth of the neoplastic cells: lepidic (formerly non mucinous brochioloalveolar adenocarcinoma), acinar, papillary, micropapillary, and solid. Of note, micropapillary pattern is a brand new histologic subtype. In addition, four variants of invasive adenocarcinoma are recognized, namely invasive mucinous (formerly mucinous brochioloalveolar adenocarcinoma), colloid, fetal, and enteric. Importantly, three variants that were considered in the previous classification have been eliminated, specifically mucinous cystadenocarcinoma, signet ring cell, and clear cell adenocarcinoma. This review presents the changes introduced by the current histological classification of lung adenocarcinoma and its prognostic implications.